2007
DOI: 10.1183/09031936.00154206
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of endotoxin-induced inflammation by taxol

Abstract: The pathogenesis of acute lung injury includes transendothelial diapedesis of leukocytes into lung tissues and disruption of endothelial/epithelial barriers leading to proteinrich oedema. In vitro studies show that the microtubule network plays a role in the regulation of endothelial permeability as well as in neutrophil locomotion. It was hypothesised that the microtubule-stabilising agent, taxol, might attenuate inflammation and vascular leak associated with acute lung injury in vivo.The effect of intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 31 publications
1
67
0
Order By: Relevance
“…This leads to a decreased ability of cells to enter size-limited pores, reflecting the process of neutrophil extravasation, which is the hallmark of RAS. The impairment of neutrophil motility by paclitaxel was also shown in an animal model of pneumonia (42). However, the experimental setup in this study did not allow dissection of the mechanisms of action since paclitaxel also acts on endothelial cells and can block secretion of proteolytic enzymes (43).…”
Section: Discussionmentioning
confidence: 98%
“…This leads to a decreased ability of cells to enter size-limited pores, reflecting the process of neutrophil extravasation, which is the hallmark of RAS. The impairment of neutrophil motility by paclitaxel was also shown in an animal model of pneumonia (42). However, the experimental setup in this study did not allow dissection of the mechanisms of action since paclitaxel also acts on endothelial cells and can block secretion of proteolytic enzymes (43).…”
Section: Discussionmentioning
confidence: 98%
“…Protein concentrations in BAL fluid were measured using an RC DC Protein Assay (Bio-Rad, Hercules, CA), as previously described (16,17). Sample readings (optical density) were converted to mg/ml, using albumin as standard (0.1-1.5 mg/ml).…”
Section: Measurements Of Bal Total Protein Albumin and Concentratiomentioning
confidence: 99%
“…Taxol is of particular importance due to its significant anti-cancerigenous activity; its natural accumulation is mainly in the cortex, although it is also stored in the aerial parts in a few species such as T. globosa and T. chinensis. In addition to the highly documented anti-cancer effect of the taxol, it has also been reported that this substance was able to decrease the effect of vascular inflammation in a model of lung injury induced by intratracheal administration of Lipopolysaccharide (LPS) (Mirzapoiazova et al, 2007). Abdominal contortion , and (4) 500 mg Kgary, suggesting a seasonal fluctuation of taxol content in the Mexican yew.…”
Section: Discussionmentioning
confidence: 99%